2020
DOI: 10.33899/ijvs.2019.126269.1282
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Salmonella enterica serovar albany in experimental infected SPF BALB/c Mice

Abstract: Salmonellosis remains an important zoonotic disease and public health concern, Salmonella enterica serovar Albany is one of the motile serovars which has been identified from poultry and humans. However, its pathogenic potentials and shedding probability and duration from infected/colonized chickens have never been reported. To assess its pathogenic potentials and shedding probability 6 SPF BALB/c mice was inoculated with 0.1ml volume for each mice bacterial solution of 10 8 CFU/ml of Salmonella entrica serova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The two-stage radial diffusion method was used for it is sensitive and important when studying the inhibiting effect of the isolated cationic peptides from camels' blood on two kinds of pathogenic bacteria (Salmonella typhimurium and Bacillus subtilis) which are known as resistant of antibiotics drugs as shown in table 1. Salmonella typhimurium is one of the bacterial serovars responsible for human and animal infections, as well as noted the increasing rate of antibiotic resistance of Salmonella typhimurium, and the ability to form endospore by Bacillus subtilis allows increasing of bacterial resistance and survival (21)(22)(23). These peptides have a positive charge that reacts and attracts the negative charge bacterial cell membranes and cell walls, as well as the presence of special receptors for these peptides on the bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…The two-stage radial diffusion method was used for it is sensitive and important when studying the inhibiting effect of the isolated cationic peptides from camels' blood on two kinds of pathogenic bacteria (Salmonella typhimurium and Bacillus subtilis) which are known as resistant of antibiotics drugs as shown in table 1. Salmonella typhimurium is one of the bacterial serovars responsible for human and animal infections, as well as noted the increasing rate of antibiotic resistance of Salmonella typhimurium, and the ability to form endospore by Bacillus subtilis allows increasing of bacterial resistance and survival (21)(22)(23). These peptides have a positive charge that reacts and attracts the negative charge bacterial cell membranes and cell walls, as well as the presence of special receptors for these peptides on the bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…The pair of the primers used to find Salmonella at genus level codifies the gene InvA that is widely distributed in Salmonella spp. (5,20,21). In addition, the reference procedure of the ISO numbered 6579-1:2017 used as a complementary test to PCR for detection the limit of salmonella conducted for all the examined samples.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is one of the most important pathogen that can infect human through ingestion of contaminated food with a sub-classification of more than 2500 serovars including Typhimurium related to foodborne salmonellosis in human (1,2). This infection can be harsh particularly in immunosuppressive people like youngest or elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be of concern as these S. Albany have the probability to cause disease with the presence of considerable numbers of virulence traits. Furthermore, Sabri et al [25] have demonstrated the pathogenesis of S. Albany by experimental mice which revealed the occurrence of haemorrhagic enteritis, cecitis and colonitis as soon as 24 hours after infection.…”
Section: Detection Of Virulence Genes In Nts Isolatesmentioning
confidence: 99%